Titanium oxide coatings formed by plasma spraying followed by induction heat treatment. Issue 2 (15th January 2023) - Koshuro, Vladimir; Osipova, Elena; Markelova, Olga; Fomina, Marina; Zakharevich, Andrey; Pichkhidze, Sergey; Fomin, Aleksandr
Abstract: Porous titanium-containing coatings were formed on titanium samples by atmospheric plasma spraying. The resulting samples were subjected to induction heat treatment in an oxygen-containing (air) atmosphere at normal pressure and treatment temperature of 650–1250 °C. As a result of experimental studies, it was established that thermal modification allowed an increase in the oxygen content in the coatings from 49.6 ± 9.2 to 71.7 ± 1.1 at.%. The change in the elemental chemical composition was accompanied by the formation of titanium oxide coatings, the surface of which was distinguished by the presence of acicular crystals of titanium oxide (TiO), anatase, and rutile (TiO2 ) with an average length of 150–200 nm and a width of about 50–100 nm. Induction heat treatment also led to an increase in the microhardness of titanium oxide coatings from 1530 ± 55 to 1825 ± 191 HV0.98 and an increase in adhesive strength.